Effect of conservative therapy for persistent postural-perceptual dizziness: a systematic review and meta-analysis - Zheng, Yaqing; Guo, Ziyan; Liu, Xinkun; Chen, He; Gang, Weijuan; Chen, Huan; Wang, Weiming (Frontiers in Psychiatry, 2025)
ObjectiveTo evaluate the effect of conservative therapy in improving function and symptom for patients with Persistent Postural-Perceptual Dizziness (PPPD) in order to provide evidence for clinical practice.MethodsRandomized controlled trials (RCTs) assessing the effect of conservative therapy for PPPD were searched in 5 databases (CNKI, Wanfang, SinoMed, PubMed and EMBASE) up to 8th March 2025. Risk of bias of included studies were assessed using Cochrane Risk-of-Bias (RoB) tool version 2. Meta-analysis was conducted where applicable.ResultsTwenty-two studies (1,764 patients) were included in this review. For selective serotonin reuptake inhibitors (SSRIs) and vestibular rehabilitation therapy (VRT), the pooled estimates presented consistent results that the combined therapy had significant improvements on Dizziness Handicap Inventory (DHI) and Hamilton Anxiety Scale (HAMA) compared with single therapy. However, the certainty of the effect of cognitive behavioral therapy (CBT) and transcranial direct current stimulation (tDCS) were unclear due to limited number of studies and small sample size. The major concern of risk of bias of included studies laid to selection of reported results and randomization process. Certainty of all outcomes were judged to be moderate to very low by using the GRADE (Grading of Recommendations Assessment, Development and Evaluation).ConclusionConservative therapies, particularly SSRIs combined with VRT or CBT, could improve functional status and symptom severity in PPPD patients with favorable safety profiles. Based on current evidence, we recommend to prioritize SSRI plus structured VRT as treatment option for patients with PPPD.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024544565.